2017
DOI: 10.1097/ncc.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Its Predictors Among Children and Adolescents With Cancer

Abstract: Routinely evaluating fatigue and school functioning in pediatric patients with cancer is warranted, as well as developing educational programs to enhance the management of fatigue and relationship issues, especially for those who were given a diagnosis recently or for late adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
1
22
0
2
Order By: Relevance
“…Furthermore, the children complaining a discomfort of TKI-therapy reported dissatisfaction with appearance, and impaired communication problems. This nding can be explained by the experience of pain, nausea and fatigue, which impaired their ability to fully participate in physical and social activities [15,34,36] . Moreover, the change in body image caused by TKI-therapy, such as weight gain, skin rash, or skin color, causes children to develop inferiority and then refuse to socialize [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the children complaining a discomfort of TKI-therapy reported dissatisfaction with appearance, and impaired communication problems. This nding can be explained by the experience of pain, nausea and fatigue, which impaired their ability to fully participate in physical and social activities [15,34,36] . Moreover, the change in body image caused by TKI-therapy, such as weight gain, skin rash, or skin color, causes children to develop inferiority and then refuse to socialize [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Female gender, living alone, severity of the malignant disease, high intensive treatment and poor response to treatment had a negative impact on HRQoL in childhood cancer survivors [4][5][6][7][8][9][10][11][12][13][14] . Meanwhile, higher education and better communication with parents are related to higher HRQoL [15][16][17] . Unlike other cancer patients, children with CML in the chronic phase (CML-CP) mainly receive long-term oral TKIs as outpatients, enabling them to participate normally in family and school life, so their HRQoL and the associated variables may also be different.…”
Section: Introductionmentioning
confidence: 99%
“…Children with cancer were the main focus of most of studies worldwide. A cross-sectional study involved 150 children aged between 7-18 years without mental illness [19] . The study found that children aged 16-18 reported lower school functioning but more sleep and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…[4567] The quality of life of children who are affected by psychosocial problems and have to cope with many stressful situations[6] is also diminishing. [89] It is for this reason that the development of psychosocial programs to support children is gaining more and more importance.…”
Section: Introductionmentioning
confidence: 99%